The Political Involvement of Kiai in the Eyes of Gus/Lora in Bondowoso, East Java - Bahar, Moh Syaeful (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
This study examines Lora's and Gus's perceptions of the involvement of kiai and pesantren in practical politics. Drawing on social construction theory and perception theory, the research explores how the political involvement of kiai is interpreted within everyday social interactions and within religious authority relations in local society. The study employs a qualitative approach through observation and in-depth interviews to understand differing viewpoints shaped by socio-cultural context, personal experience, and political dynamics. Findings reveal that perceptions are divided into positive and negative orientations. Positive perceptions consist of passive acceptance and active support for kiai participation in politics, while negative perceptions appear in confrontational and accommodative forms. Theological considerations, sociological relations, emotional bonds, economic interests, and inter-kiai competition influence these perceptions. The study concludes that political engagement of kiai produces both social integration and disintegration, while simultaneously opening political participation and generating new negotiations of religious authority in contemporary local politics.